Differences in the biomechanical behaviors of natural teeth and dental implants. Issue 4 (April 2021) - Chang, Hao-Hueng; Yeh, Chun-Liang; Wang, Yin-Lin; Huang, Yi-Chao; Tsai, Shang-Jye; Li, Yu-Ting; Yang, Ju-Hsuan; Lin, Chun-Pin
Abstract: Objective: The lack of a PDL, which acts as an energy absorber, is a contributor to implants' early failure; however, these discrepancies are not well understood because of limited in vivo research. This study investigated the discrepancy in biomechanical behaviors between natural teeth and dental implants by detecting micro-movements in vivo. Methods: We designed a device that could measure precisely mechanical behaviors such as creep, stress relaxation, and hysteresis by using load–control displacement on teeth and implants. We also compared energy dissipation between natural teeth and dental implants by subtracting the area of the hysteresis loop of natural teeth from that of dental implants. Results: Biphasic curves with an initial phase of rapid response and a subsequent phase of slow response were confirmed in creep and stress relaxation curves for the load–time relationship in natural teeth. By contrast, the behavior of creep or stress relaxation was less prominent when the dental implants were tested. We observed that the periodontal ligament under an axial intrusive load of 300 g in a loading rate 3 g/s could dissipate the energy of 7.35 ± 1.18 × 10 −2 mJ, approximately 50 times that of the dental implants (1.47 ± 1.22 × 10 −3 ) with statistically significant ( p < 0.05). Significance: We confirmed natural teeth could achieve greater energy dissipation compared to dental implants, which owe to that natural teeth exhibited fluid and viscoelastic properties.